Kualitas Kimia Serat beberapa Klon Rami Asal Sumatera Barat - Denny Yulfa; Reni Mayerni; Yusniwati Yusniwati (Agrotechnology Research Journal, 2019)
Flax/jute is natural fiber plants that that produce fiber from the bark. Ramie fiber has a better quality than the others natural fiber, so it can meet fiber the increase needs cultivar with the best chemical composition of fiber. The aim of this study was to detect the chemical composition of fiber in several clones of ramie from West Sumatera. The study was conducted on December 2018 at the Laboratory of Technology Agriculture Product Andalas University for analyzed the content of chemical composition (water, ash, holocellulose, cellulose, hemicellulose, and lignin). The result of this study showed that the highest level of water content, ash, hemicellulose, and lignin were found in Situjuah clones those are 40.43, 6.74, 14.39, and 9.98% respectively. Whereas for the highest level of holocellulose and cellulose contents were in Ramindo 1 clone those were 70.23 and 58.46% respectively.